Pengaruh Suplementasi Vitamin A pada Pengobatan Pasien TB Paru terhadap Percepatan Konversi Dahak pada Fase Intensif Di Wilayah Kerja Puskesmas Kecamatan Medan Kota - Alexander Marpaung; Parluhutan Siagian; Dina Keumala Sari (Fakultas Farmasi Universitas Pancasila, 2018)
Indonesia is the second rank for the most TB (Tuberculosis) cases in the world after India. It’s estimated there are a million cases per year in Indonesia. The objective of the research was to find out the influence of Vitamin A supplementation in the medication of pulmonary TB on the acceleration of sputum conversion time at intensive phase in the Working Area of Puskesmas in Medan Kota Subdistrict. This research applied clinical testing design with experimental approach and Experimental Quasi method. The samples were 30 newly diagnosed pulmonary TB patients consisting of 15 patients in the treatment group and 15 patients in the control group. They were ≥ 18 years old, regularly consumed category I OAT with BMI ≥ 18.5. The statistical data were analyzed by Mann-Whitney statistical testing at reliability rate 95% (p < 0.05). The results of the research on the treatment group discovered that they were mostly 18-27 years old 40.0%, male 73.3%, mostly university students 26.7%, had BTA conversion in the second week 80.0%; and the sputumconversion time was 2.4 weeks in average. The results of the research on the control group demonstrated that they were mostly 18-27 years old 33.3%, male 80.0%, mostly university students and entrepreneurs 20.0%, had BTA conversion in the second week 80%; and the sputum conversion time was 4.1 weeks in average. Vitamin A supplementation in the medication of pulmonary TB patients had some influence on the acceleration of sputum conversion at intensive phase (p = <0.001) < (alpha = 0.05). Vitamin A supplementation in the medication of pulmonary TB patients had some influence on the acceleration of sputum conversion at intensive phase in the Working Area of Puskesmas in Medan Kota Subdistrict. speed up wound healing on second degree burns. White egg gel had significantly difference compared to negative control of NaCl 0.9% and no signifi cantly difference compared to Bioplacenton as positive control.